Program Klinik Jurnal ; Upaya Menstimulasi Minat Tulis Mahasiswa di Perguruan Tinggi - Fathor Rozi; Nur Hayati (MANAZHIM, 2023)
This study aims to provide understanding and train students in stimulating students' writing interest in higher education. This research was conducted at Nurul Jadid Paiton University Probolinggo with a qualitative approach with the type of research in the field (field researcb). Data obtained from the observation process, interviews with speakers and students. In the process of data analysis, researchers carry out data collection, data reduction, data presentation, and conclusion of data findings. The results of the study showed the success of the journal clinic program in Nurul Jadid University students. The process of this activity is through training Providing continuous coaching, Understanding the structure of articles, Conducting regular practice and Providing motivation in the spirit of work. This clinic program successfully overcomes students' difficulties in stimulating writing interest. This training is able to provide a stimulus to stimulate students to love writing by holding a journal clinic program. This training has been able to improve the knowledge, skills, and motivation of students to write scientific articles.